2021
DOI: 10.1007/s00221-021-06231-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost brain computer interface for everyday use

Abstract: With the growth in electroencephalography (EEG) based applications the demand for affordable consumer solutions is increasing. Here we describe a compact, low-cost EEG device suitable for daily use. The data are transferred from the device to a personal server using the TCP-IP protocol, allowing for wireless operation and a decent range of motion for the user. The device is compact, having a circular shape with a radius of only 25 mm, which would allow for comfortable daily use during both daytime and nighttim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…What sets this ADC apart from its competitors is its built-in multiplexer. Usman et al [15] and Rakhmatulin et al [16] extensively reviewed the capabilities of this ADC and the features of the ADS1299 multiplexer, a discussion that is beyond the scope of this article. Prior to testing, impedance was verified using the ADS1299 function following the methodology outlined in the article [17].…”
Section: Technical Realizationsmentioning
confidence: 99%
“…What sets this ADC apart from its competitors is its built-in multiplexer. Usman et al [15] and Rakhmatulin et al [16] extensively reviewed the capabilities of this ADC and the features of the ADS1299 multiplexer, a discussion that is beyond the scope of this article. Prior to testing, impedance was verified using the ADS1299 function following the methodology outlined in the article [17].…”
Section: Technical Realizationsmentioning
confidence: 99%
“…Similar to open-source software, open hardware initiatives have also been instrumental in pushing innovation in electrical circuits for neural interfaces. In the BCI industry, such as OpenBCI and several BCI research labs (Rakhmatulin et al, 2021 ), have demonstrated how to build low-cost BCIs with consumer electrical components.…”
Section: Macro-trends In Neurotechnology Developmentmentioning
confidence: 99%
“…What sets this ADC apart from its competitors is its builtin multiplexer. Usman et al [15] and Rakhmatulin et al [16] extensively reviewed the capabilities of this ADC and the features of the ADS1299 multiplexer, a discussion that is beyond the scope of this article. Prior to testing, impedance was verified using the ADS1299 function following the methodology outlined in the article [17].…”
Section: Technical Realizationsmentioning
confidence: 99%